Geodetic Sciences Theory, Applications and Recent Developments - Erol, Bihter; Erol, Serdar (IntechOpen, 2021)
Advances in space-borne technologies lead to improvements in observations and have a notable impact on geodesy and its applications. As a consequence of these improvements in data accuracies, spatial and temporal resolutions, as well as the developments in the methodologies, more detailed analyses of the Earth and a deeper understanding of its state and dynamic processes are possible today. From this perspective, this book is a collection of the selected reviews and case-study articles that report the advances in methodology and applications in geodesy. The chapters in the book are mainly dedicated to the Earth's gravity field theory and applications, sea level monitoring and analysis, navigation satellite systems data and applications, and monitoring networks for tectonic deformations. This collection is a current state analysis of the geodetic research in theory and applications in today's modern world.